Impact of the Late Miocene Cooling on the loss of coral reefs in the Central Indo-Pacific - B. F. Petrick; L. Reuning; M. Pfeiffer; G. Auer; L. Schwark (Climate of the Past)
The Late Miocene Cooling (LMC) has been recognized as a global event in the climate record and posited as the start of modern ecosystems. Whereas climate shifts in modern tropical terrestrial ecosystems around 7.0–5.4 Ma are known, little is known about the impact of the LMC on coral reefs, where few good proxy records exist. During the Pliocene, a stratigraphic interval is present in the Central Indo-Pacific, where reefs that were present at the start of the Messinian disappeared by the Early Pliocene. This “Pliocene Reef Gap” has often been ascribed to non-climatic factors. However, a lack of proxy data prevents an understanding of climatic changes during this time. Here, we present a TEX<msubsup>86H</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="11pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="2a07f66c340e5ca419639b2784f7d244"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="cp-21-405-2025-ie00001.svg" width="11pt" height="17pt" src="cp-21-405-2025-ie00001.png"/></svg:svg>-based sea surface temperature (SST) record for the Coral Sea, suggesting that the LMC is present across the Central Indo-Pacific. During the LMC, SST at ODP Site 811 declined by about 2 °C, while cooling lasted from 7.0 to 5.4 Ma. This cooling has also been seen in other parts of the Central Indo-Pacific. The LMC caused many changes in the Central Indo-Pacific, including a southwest shift in the monsoon belt, changes in terrestrial inputs, and changes in the strength of ocean currents. All of these factors can be stressors affecting coral reef growth. This suggests the overall impact of the LMC was to increase the stress on reef systems, which could have provided a driver for the collapse of individual reefs and therefore a potential cause for the Pliocene Reef Gap. The change in SST and other stressors associated with the cooling caused coral reef systems to collapse across the Central Indo-Pacific.